Wybór pism. [Pod red. T. Daniszewskiego, J. Kancewicza i J. Kowalskiego. Z wst. J. Kancewicza] ("Ksia̜żka i Wiedza", 1967)
Z bibliogr., il-mi, indeks-mi i prt-mi. Zakład Historii Partii przy KC PZPR. 1. 1905-1918. [Oprac. J. Kancewicz i J. Kasprzakowa]. 471